Norman Mailer’s The Naked and the Dead as a Novel of Manners - Khallaf, Muhammad (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Norman Mailer (1923-2007) is one the most important figures among the American Writers, an extremely influenced personality in the post-world war II American Literature. He is best known for his first war novel The Naked and the Dead (1948), which is a commentary on the American society. Hence, the present study is an attempt to investigate and reflect the social ills and fragmentation, misery and the overwhelming social and political restraints that formed the American atmosphere at that time. Mailer is interested in what happens in the contemporary American society. His aim is to depict the national rituals of American life. The researcher in this study seeks to identify the literary aspects reflected and drawn in The Naked and the Dead that make us categorize it as a novel of manners for it is satiric and realistic in depiction, in which Mailer unprecedentedly characterizes the social mores, evils and customs that are characteristic of a particular class of people in a specific historical context. The descriptive approach along with detailed analysis is utilized in conducting the present study. The conclusion sums up the most important findings of the study.